1980
DOI: 10.1093/ajcn/33.7.1667
|View full text |Cite
|
Sign up to set email alerts
|

Conservative treatment with ketoacid and amino acid supplemented low-protein diets in chronic renal failure

Abstract: Twenty-six patients with advanced renal failure (glomerular filtration rate less than 6 ml/min) were treated with a mixed quality low protein diet and ketoacid analogues. An improvement in nitrogen balance, serum transferrin and phosphate, and base excess was observed after 2 weeks of treatment. In a longer term study, the result of 20 patients treated with ketoacids for up to 14 months were compared to a group 40 patients who received a low-protein diet with essential amino acids. Patients responded similarly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
10
0

Year Published

1983
1983
2018
2018

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…These findings seem to be supported by the fact that a number of uremic symptoms may be improved by para thyroidectomy [1, 4,5]. Our previous studies showed a decline of elevated PTH levels in patients treated with a low-protein diet and substitution of a mixture of essential amino acids or their a-keto analogues (K A) [7,8], respec tively. These observations were in agreement with the results of Barsotti et al [3].…”
Section: Introductionmentioning
confidence: 87%
“…These findings seem to be supported by the fact that a number of uremic symptoms may be improved by para thyroidectomy [1, 4,5]. Our previous studies showed a decline of elevated PTH levels in patients treated with a low-protein diet and substitution of a mixture of essential amino acids or their a-keto analogues (K A) [7,8], respec tively. These observations were in agreement with the results of Barsotti et al [3].…”
Section: Introductionmentioning
confidence: 87%
“…Besides the cost-effectiveness issue, to the authors' knowledge, until this date, no other study in literature was designed to investigate the effect of ketoanalogues in dogs with chronic kidney disease. Although one case report described the effectiveness of ketoanalogues when associated with a low protein diet (Veado et al 2002), all the literature is focused in humans (Frohling et al 1980, Jones et al 1983, Mitch et al 1984, Tóth et al 2012, Teplan et al 2000, Prakash et al 2004, Thilly 2013.…”
Section: Introductionmentioning
confidence: 99%
“…Attempts to control these abnormalities include dietary phosphorus restriction, prescription of calcium carbonate to reduce phosphate absorption from the gut, and treatment with calcitriol [2]. In addition, previous studies showed a decline of elevated PTH levels in patients treated with a low-protein diet and substitution of mixture of essential amino acids or their ·-keto analogues (KA) [3,4], respectively. These observations were in agreement with the results of chronic hemodialysis patients who received a high-protein diet during a 3 months' administration of KA [5].…”
mentioning
confidence: 99%